Development of a constructive solution of wood columns and crossbars interfaces on metal overlays and screws - M. A. Dezhin; A. M. Ibragimov (Vestnik MGSU)
Introduction. The paper discusses the advantages and features of the main existing methods of connecting wooden columns and crossbars.Materials and methods. It was proposed to increase the load-bearing capacity and reduce the deformability of joints by modifying the joints with the introduction of epoxy resin between the screw and the wood and between the overlay and the end of the wooden element to which it is attached and modifying the design of the overlays.Results. As a result, a constructive solution for connecting wooden columns and crossbars was developed, which has increased reliability compared to the studied connections and is free of their disadvantages. This result was achieved due to the presence of an adhesive layer between the screw and the wood, as well as between the overlay and the wooden element, the making of notches on the sides of the overlays attached to the wooden elements, the increased length of the screws screwed into the overlay with a groove, compared to the length of the screws screwed into an overlay with a tenon, placement of holes for screws at an angle of 90° to the surface of the overlay into which the screws are screwed.Conclusions. An urgent issue is the development of constructive solutions for connections of wooden elements, in particular the interfaces of columns and crossbars. The paper discusses the advantages and features of the main existing methods of connecting wooden columns and crossbars.